How journalism experience translates to social entrepreneurship: An intention formation study of the Art Yard at Dadaocheng in Taiwan - Huei-Ching Liu; Chaoyun Liang (Journal of Entrepreneurship, Management and Innovation)
Purpose: In this study, the story of the Art Yard at Dadaocheng, Taipei, Taiwan, was adopted as a case study. We thoroughly investigated the founder, a former television reporter, and her social entrepreneurial intention (SEI) to initiate a social enterprise. Methodology: By integrating the two classic models of entrepreneurship intention, entrepreneurial event theory and theory of planned behavior, we investigated the antecedents of SEI (i.e., empathy, entrepreneurial alertness, entrepreneurial self-efficacy, social responsibility, and social capital and support). Findings: The founder possessed capability of communication and coordination because of her professional journalism experience and successfully introduced her passionate empathy and profound sense of social responsibility into her entrepreneurial aspirations. Her entrepreneurial alertness and self-disciplined entrepreneurial self-efficacy originated from in-service education and inspiration through action. Social networks accumulated during her journalism career did not represent the primary source of support when establishing her social enterprise. In this research, two additional antecedents of SEI were identified: knowledge capital and work experience. Implications for theory and practice: Social entrepreneurial attitudes can be developed on the basis of passionate empathy and social entrepreneurial alertness is required to address the professional development needs in service programs. Social entrepreneurial self-efficacy in communication and marketing management is closely associated with the journalism profession, and the journalistic passion for social justice can motivate social responsibility activities. Careful selection, maintenance, and transformation of business partners for social support are essential. Originality and value: A new SEI theory was subsequently proposed for future research, and practical implications were addressed for social entrepreneurship.